Anthropological Sociology Of Sharia Economic Law On The Practice Of Gold Arisan Contracts Of Indonesian Sharia Pawnshops - Mida Safitriani, Mida Safitriani; Arifin, Tajul; Abdal, Abdal; Rizqillah, Faisal Najmi (CV. Strata Persada Academia, 2023)
This research analyzes in depth the practice of gold gathering at Sharia Pawnshop from the perspective of sociology, anthropology and sharia economic law to reveal the complex dynamics in modern sharia economic practices and their impact on wider society. This understanding also provides insight into how local traditions and global norms interact in increasingly complex contexts. The author uses qualitative research methods and secondary data analysis. These data will be analyzed using sociological and anthropological theoretical approaches to sharia economic law. The results of this research are that the Gold Arisan practice at Sharia Pawnshop is a collective system of buying gold like traditional arisan. It builds social relationships, reflects cultural values, and adheres to sharia economic principles without usury. Sharia economic laws such as Qardh, Murabahah, and Rahn play an important role. Sociologically, this forms a complex social network. From an anthropological perspective, it reflects the values ​​and traditions of society. From the perspective of economic sharia law, comply with strict principles including the prohibition of usury and asset management. This analysis provides an in-depth understanding of financial practices in the context of culture, social norms and Islamic law, as well as the impact of social interactions.